2016
DOI: 10.1016/j.ijid.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium tertium in neutropenic patients: case series at a cancer institute

Abstract: The unusual susceptibility pattern of C. tertium, with resistance to beta-lactams and clindamycin, likely explains its presence in immunosuppressed patients. Vancomycin remains the drug of choice. The pathogen continues to have a low virulence and a low mortality when treated appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…Clostridium tertium is an anaerobic gram-positive bacterium in the phylum Firmicutes. Although C. tertium has traditionally been considered non-pathogenic, various studies have reported it to be a significant cause of bacteremia and other infections in neutropenia patients [29,49,50,53,60]. In addition, C. tertium infections in non-neutropenic patients have also been reported recently [57,58,62].…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium tertium is an anaerobic gram-positive bacterium in the phylum Firmicutes. Although C. tertium has traditionally been considered non-pathogenic, various studies have reported it to be a significant cause of bacteremia and other infections in neutropenia patients [29,49,50,53,60]. In addition, C. tertium infections in non-neutropenic patients have also been reported recently [57,58,62].…”
Section: Discussionmentioning
confidence: 99%
“…A C. tertium infection usually presents as fever and gastrointestinal complaints, such as abdominal pain, rectal bleeding, nausea, diarrhea, or constipation. Some patients with a C. tertium infection can be completely asymptomatic [5] while immunocompromised patients can have septicemia.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al conducted a retrospective review of patients with C. tertium bacteremia at H. Lee Moffitt Cancer Center and Research Institute from 2005 to 2015 and found that only seven patients were diagnosed in this 10-year period. All patients were neutropenic: five had acute myeloid leukemia and two had myelodysplastic syndrome [5]. Despite the clearance of blood cultures in all seven cases within three days of antibiotic therapy, five patients died within four months of C. tertium bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Colonization by C. paraputrificum is mainly associated with myonecrosis and bacteremia in humans although a wide range of invasive infections can also occur [13], and this pathogen was recently found to be the fortuitous cause of necrotizing cellulitis of the abdominal wall in one individual [14]. C. tertium is associated with bacteremia cases [15] and septic shock [16], but it mainly infects immunocompromised [17] and neutropenic patients [18]. This species has recently been identified as a causal agent of necrotizing fasciitis and gangrene [19], and is also known to cause various pathologies in non-neutropenic patients [20].…”
Section: Introductionmentioning
confidence: 99%